Design and performance study of the LEPD silicon tracker onboard the CSES satellite - 吴峰 王焕玉 赵小芸 孟祥承 徐岩冰 王辉 马宇蒨 卢红 王平 石峰 李新乔 蒋文奇 安振华 于晓霞 刘汉一 (Chinese physics C, 2013)
The low energy particle detector （LEPD） is one of the main payloads onboard the China seismic electromagnetic satellite （CSES）. The detector is designed to ascertain space electrons （0.1–10 MeV） and protons （2–50 MeV）. It has the capability of identifying the electrons and protons, to measure the energy spectrum and the incident angle of the particles. The LEPD is made up of a silicon tracker system, a CsI （Tl） mini-calorimeter, an anti-coincidence system made by plastic scintillator, as well as electronics and a data acquisition system （DAQ）. The tracker is also a kind of E-E telescope; it consists of two layers of double-sided silicon strip detectors （DSSD）. The signals emerging from the silicon tracker can be read out by two pieces of application specific integrated circuit （ASIC）, which also can generate an event trigger for the LEPD. The functions of the DSSD system in the LEPD for charged particles were tested by 241Am @5.486 MeV α particles. The results show that the DSSD system works well, and has high performance to detect charged particles and measure the position of incident particles.